2011
DOI: 10.1002/ep.10607
|View full text |Cite
|
Sign up to set email alerts
|

Effect of injector opening pressure on performance, emission and combustion characteristics of DI diesel engine fueled with diesel and honne oil methyl ester

Abstract: Honne oil methyl ester (HOME), a nonedible vegetable oil has remained as an untapped new possible source of alternative fuel. The present research is aimed to investigate experimentally the performance, exhaust emission, and combustion characteristics of a DI diesel engine, when fueled with neat diesel (ND) and HOME. The injector opening pressure (IOP) is varied from 200 bar (manufacturer specified value) to 260 bar in steps of 20 bar. The combustion parameters of HOME (IOP 260 bar) are found to be very close … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The liquid water is cooled and sent back to a water tank (5). A recuperator is installed downstream the separator to heat the high-pressure air (4). Within the recuperator, the air is heated by the exhaust flow (7), and then an intra-cylinder heat recovery process is achieved.…”
Section: Description Of the Split Engine Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…The liquid water is cooled and sent back to a water tank (5). A recuperator is installed downstream the separator to heat the high-pressure air (4). Within the recuperator, the air is heated by the exhaust flow (7), and then an intra-cylinder heat recovery process is achieved.…”
Section: Description Of the Split Engine Cyclementioning
confidence: 99%
“…The high power density, good transient response and low cost make the ICE an excellent fit with the needs of road vehicles in an environment with an abundant supply of low cost liquid fossil fuels [1][2][3]. However, climate change and diminishing stocks of petroleum have led to a drive for higher efficiency solutions [4,5]. Alternative power converters such as fuel cells and batteries and increased electrification of the transmission between the prime mover and the wheels and downsizing of the ICE have also been proposed to improve the vehicle system performance [6].…”
Section: Introductionmentioning
confidence: 99%
“…They reported that, for JMETPO20 at 220 bar pressure the brake thermal efficiency was marginally improved and decreased the HC, CO and smoke emissions. Venkanna and Venkataramana Reddy investigated experimentally the performance, exhaust emission, and combustion characteristics of a DI diesel engine, when fueled with neat diesel (ND) and Honne oil methyl ester (HOME). The injector opening pressure (IOP) is varied from 200 bar (manufacturer specified value) to 260 bar in steps of 20 bar.…”
Section: Introductionmentioning
confidence: 99%
“…Diesel engines are extensively applied in transportation field and manufacturing industry due to their high thermal efficiency and reliable performance. However, diesel engines still have major problems of simultaneous reduce nitrogen oxide (NOx) and smoke emissions due to diffusion‐governing combustion mechanisms . Many new combustion modes such as homogenous charge compression ignition and dual‐fuel have been proposed to overcome this problem .…”
Section: Introductionmentioning
confidence: 99%